An unanticipated decline in the caesarean section rate. (7th June 2011) - Walsh, C E; Burke, G
Abstract : Aim: The persistent rise in the rate of caesarean section (CS) is a prominent and contentious feature of modern obstetrics. The aim of this study was to determine which clinical subgroups contributed to an unexpected decline in the CS rate at our institution and to discuss the contributory factors that may have been involved. Methods: We used prospectively digitized data to classify CS according to the Robson Classification. We compared data for the years 2006 and 2009 to determine the contributions of the discrete clinical groups to the overall CS rate. Fisher's exact test was used for statistical analysis. Results: In 2006, there were 4596 deliveries, of which 1427 were caesarean (31%); in 2009, there were 4991 deliveries, of which 1363 were caesarean (27.3%), a decline of 3.7% in the 3-year period (p<0.0001). There was a decline in the contribution of each of groups 1 to 5. The decline was statistically significant only in Group 2A (nulliparous, singleton, cephalic, ≥ 37 weeks, induced labour), where the CS rate fell from 33% to 23% (p<0.001). The 10% decrease in the CS rate in Group 2A contributed one-third of the overall decline. Changes in induction and labour management policy after 2006 included the introduction of intrapartum fetal blood sampling; the replacement of prostaglandin tablets with gel; and a lower dose oxytocin regime. Conclusion: Robson Group 2A was the largest contributor to a 3.7% decline in the CS rate over a 3-year period.